Strategies for Reading Visual Poetry: A Semiotic Approach and Its Practical Application - Katkuvienė, Jurgita (Semiotika, 2022)
The article explores the ways in which the Greimasian method of semiotics can be applied to the analysis of contemporary Lithuanian poetry texts, specifically visual poetry. Bearing in mind the nature of visual poetry, I consider a semiotic approach, which allows explaining the strategies of meaning making in visual poetry. The methodological question goes back to the origins of Algirdas Julius Greimas’ semiotics, in particular the works of Louis Hjelmslev. I draw attention that based on Hjelmslev’s approach, it is important not only to treat any unit of meaning as a certain relationship between the plane of content and the plane of expression, but in the case of visual poetry, also to supplement it with a more detailed description of Hjelmslev’s levels of language (form–substance–purport) and their interrelations. It calls attention to the plane of expression, which has a special status in visual poetry. I argue that one of the most important conditions for the emergence of signification in visual poetry is the phenomenon of unstable correlation, which is a semiotic relationship between the plane of expression and the plane of content that appears as a process of production of reciprocal presupposition, which, in turn, is dependent on the focus point of reader’s gaze. In the first part of the article, in which I address theoretical considerations regarding all the above-mentioned topics, I examine how the model of structural linguistics can assist in complementing the semiotic analysis of visual poetry. In the second part, I analyze two works by contemporary Lithuanian visual poets using the proposed model of meaning creation: “PASTAZENKLAS ISLEISTAS KREPSINIO CEMPIJONATUJ” (“A POSTALSTAMP ISSUED FOR THE FOOTBALL CHEMPIONSHIP”) by Gytis Norvilas (2006) and “om rekonstrukcija I“ (“om reconstruction I”) by Donaldas Apanavičius from his three-poem cycle (1999). The analysis reveals the points of unstable correlation and various reading possibilities.